(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2026)
This study investigates the global transmission of geopolitical oil price shocks within the context of the energy transition era (2000–2025). Employing a Panel Autoregressive Distributed Lag (PARDL) framework, estimated via Mean Group (MG) and Pooled Mean Group (PMG) techniques, the research analyzes a diverse panel comprising global economic powers—the USA, China, the Euro_Area, Russia, and Saudi Arabia—alongside emerging African oil producers, Nigeria and Angola. Data for the study variables, including Real GDP Growth (RGDPG), Real Exchange Rate (LNRER), Interest Rates (INTR), Global Oil Prices (LNGOP), and Global Real Economic Activity (GREA) were sourced from the World Bank’s WDI, IMF International Financial Statistics, and the U.S. EIA, with a binary dummy capturing the Russian Sanctions (SAN) era. The empirical results, validated by the Hausman test, justify the PMG estimator and reveal a significant long-run equilibrium across the variables. A central finding is the confirmation of strong cross-sectional dependence via the Pesaran CD test, proving that geopolitical shocks—such as the Russian sanctions and the US-Israel-Iran tensions—are instantaneously transmitted across the panel. While global real economic activity serves as a robust driver of growth, the study identifies a contractionary long-run impact of sustained high global oil prices and interest rates. It further reveals that real exchange rate supports long-term economic expansion, but its immediate effect on growth is not significant in the short-run. Furthermore, the high speed of adjustment evidenced by the error correction term highlights a degree of macroeconomic resilience. Notably, the sanctions dummy was statistically insignificant as a direct shock, suggesting that geopolitical conflicts impact emerging producers primarily through the mediation of global demand and price volatility. The study concludes that as the energy transition accelerates, producers must shift toward aggressive economic diversification and regional integration to mitigate the risks of global shock transmission.